Sliding Sector-Based Controller for Regulating Voltage/Frequency in Autonomous Microgrid - Thakur A.K.; Singh S.P.; Singh S.; Sachan A. (My University, 2025)
The application of microgrids (MG) has a vital role in grid modernization. However, a larger number of installations of electronically coupled distributed energy resources (DER) units in MGs have created opportunities and threats for grid operations. Therefore, efficient and reliable control strategies for MG operation are essential. This article introduces the concept of sector design to show the stabilization of voltage source converter-interfaced DER units in MG applications. The sliding sector design is advanced sliding mode control to obtain a region of attraction such that the state space is divided into attractive and nonattractive regions. In addition, a variable structure-based controlling method has been introduced to drive the trajectories of a plant from the exterior to the interior of the sector and strictly inside throughout the process. In autonomous MG operation, the proposed controller focuses on stabilizing the electronically coupled DER unit’s voltage and frequency response. Besides, it confirms the safety of the power conversion system from external disturbances. The system stability is proven using the Lyapunov candidate function. The proposed strategy has been effectively validated through PSCAD/EMTDC. The simulation results have examined the impact of balanced, unbalanced, nonlinear, and dynamic loading patterns in islanded MG. © 2023 Taylor & Francis Group, LLC.